Arroz: Implicancia del peso específico de granos en la calidad de semillas - Gómez Ibarra, R. A. (Universidad Nacional del Litoral, 2021)
Size and speciﬁc gravity (SG) of seeds affects their quality and, in rice, these variations explain differences. In order to relate morphometric variables with physiological quality parameters, length, width, weight of 1000 seeds, germinating power and energy, plant stand and vigor were evaluated in 4 rice cultivars fractionated by SG. The percentage distribution of SG categories differs between cultivars. The seeds ranged between 9.30-10.50 mm in length and 2.41-2.75 mm in width, with signiﬁcant effects of cultivar and SG. In 1000 seeds weight, PAC 103 stood out for its greater mass and a gradient was evidenced according to the SG category. Germinating power, percentage of normal and abnormal plants and ungerminated seeds, germination energy and plant stand were affected by SG. Seeds with PE <1.14 g/cm3 showed a worse performance in these parameters.